Single-molecule states link transcription factor binding to gene expression - Doughty, Benjamin R.; Hinks, Michaela M.; Schaepe, Julia M.; Marinov, Georgi K.; Thurm, Abby R.; Rios-Martinez, Carolina; Parks, Benjamin E.; Tan, Yingxuan; Marklund, Emil; Dubocanin, Danilo; Bintu, Lacramioara; Greenleaf, William J. (Nature (London), 2024)
The binding of multiple transcription factors (TFs) to genomic enhancers drives gene expression in mammalian cells 1 . However, the molecular details that link enhancer sequence to TF binding, promoter state and transcription levels remain unclear. Here we applied single-molecule footprinting 2 , 3 to measure the simultaneous occupancy of TFs, nucleosomes and other regulatory proteins on engineered enhancer–promoter constructs with variable numbers of TF binding sites for both a synthetic TF and an endogenous TF involved in the type I interferon response. Although TF binding events on nucleosome-free DNA are independent, activation domains recruit cofactors that destabilize nucleosomes, driving observed TF binding cooperativity. Average TF occupancy linearly determines promoter activity, and we decompose TF strength into separable binding and activation terms. Finally, we develop thermodynamic and kinetic models that quantitatively predict both the enhancer binding microstates and gene expression dynamics. This work provides a template for the quantitative dissection of distinct contributors to gene expression, including TF activation domains, concentration, binding affinity, binding site configuration and recruitment of chromatin regulators. A study uses single-molecule footprinting to measure protein occupancy at regulatory elements on individual molecules in human cells and describes how different properties of transcription factor binding contribute to gene expression.